A Systematic Literature Review and Meta-Analysis of AIML Experience in Banks - Upadhaya, Sashi; Khanal, Jibit (Namuna Academic Journal, 2023)
The prime concern of this research article is to engender the existing knowledge, trends and gaps in AIML in bank domains. Additionally, the article focuses on the applications of PSALSAR framework for conducting systematic literature review and meta- analysis of artificial intelligence (machine- learning) adoption in banks. Under the PSALSAR (Protocol, Screening, Appraisal, Synthesizing, Analysis and Reporting) framework PICOC (Population, Intervention, Comparison, Outcome and Context) method is also used to define the research scope. Although meta- analysis is useful for both the qualitative and quantitative content analysis, only the qualitative aspects are considered in this research article.